Leisure Time Habits and Levels of Physical Activity in Children and Adolescents - Juan-José M; Beatriz Polo-Recuero; Adrián Solera-Alfonso; Alberto Arribas-Romano; Miriam García-González; Sofía Laguarta-Val; José Manuel Delfa- (MDPI AG, 2024)
Background/Objectives: Childhood and adolescence are important stages of life for acquiring healthy habits. There is a high prevalence of sedentary lifestyles worldwide during these ages, which negatively impacts health. This is attributed, in part, to excessive time spent engaging in sedentary behaviors. The aim of this study was to assess the time spent on sedentary behaviors and their relationship with physical activity levels in children and adolescents in the Community of Madrid. Methods:A total of 26,729 participants aged 10-17 from various schools and institutes took part in this study. The International Physical Activity Questionnaire Short Form (IPAQ-SF) was used, and they were asked about the time they spent on different leisure time habits (specific sedentary behaviors and organized physical activity). A generalized linear model was used to analyze the association between the time spent in sedentary activities and the time spent in physical activity. Results: The results revealed that children and adolescents engage in low levels of physical activity and most of them spend considerable time in sedentary behaviors such as studying, watching television, or using social media. Completing school homework (Coef: 1.23, 95% CI: −0.51 to 2.97, p = 0.167) or using social media for more than 2 h (Coef: 1.29, 95% CI: −2.98 to 0.40, p = 0.133) compared to not dedicating time to them did not show a significant association with daily physical activity time. Watching television for more than 2 h was associated with a decrease of 2.60 min (95% CI: −4.41 to −0.78, p = 0.005). Thus, no or only irrelevant associations were found between time spent in sedentary activities and physical activity time. Conclusions: Despite the drawbacks of spending time engaging in sedentary behaviors, they seem to be compatible with physical activity levels. Therefore, it is important to continue research on physical activity adherence strategies to promote overall health and well-being.